Production of cowpea crop under salinity and growth regulator - Oliveira, Francisco de A. de; Medeiros, Jose F. de; Alves, Rita de C. [UNESP]; Lima, Luan A.; Santos, Sandy T. dos; Regis, Lucia R. de L. (Univ Federal Campina Grande, 2015)
The efficient use of saline water depends on the tolerance of crop and technology adoption to reduce the effect of salinity. The present study was conducted with the objective to evaluate the use of the growth promoter Stimulate(center dot) on cowpea plants under saline conditions. The experimental design was completely randomized, in a 4 x 4 arrangement, composed of four levels of salinity of irrigation water (0.5, 2.0, 3.5 and 5.0 dS m(-1)) and four levels of Stimulate(center dot) (0, 0.5, 1.0 and 1.5 L ha(-1)), with four replications. The following variables were analysed: number of pods plant(-1), pod length, number of grains pod(-1), grain yield and harvest index. Statistical analysis of the data revealed that there was significant interaction between the factors for most variables. The use of high concentrations of growth promoter enhances the deleterious effects of salinity, as well as the use of irrigation water of high salinity inhibits the beneficial effect of plant growth regulator in crop yield. The use of biostimulant Stimulate(center dot) with concentrations of 0.5 to 0.75 L ha(-1) provides an increase in grain yield of cowpea, provided that irrigation is performed with water of electrical conductivity less than 3.5 dS m(-1).
Keywords: Vigna unguiculata (L.) Walp.; salt stress; plant regulators